Impaired Letter-String Processing in Developmental Dyslexia: What Visual-to-Phonology Code Mapping Disorder? - Valdois S; Lassus-Sangosse D; Lobier M (Dyslexia (10769242), 2012)
Poor parallel letter-string processing in developmental dyslexia was taken as evidence of poor visual attention (VA) span, that is, a limitation of visual attentional resources that affects multi-character processing. However, the use of letter stimuli in oral report tasks was challenged on its capacity to highlight a VA span disorder. In particular, report of poor letter/digit-string processing but preserved symbol-string processing was viewed as evidence of poor visual-to-phonology code mapping, in line with the phonological theory of developmental dyslexia. We assessed here the visual-to-phonological-code mapping disorder hypothesis. In Experiment 1, letter-string, digit-string and colour-string processing was assessed to disentangle a phonological versus visual familiarity account of the letter/digit versus symbol dissociation. Against a visual-to-phonological-code mapping disorder but in support of a familiarity account, results showed poor letter/digit-string processing but preserved colour-string processing in dyslexic children. In Experiment 2, two tasks of letter-string report were used, one of which was performed simultaneously to a high-taxing phonological task. Results show that dyslexic children are similarly impaired in letter-string report whether a concurrent phonological task is simultaneously performed or not. Taken together, these results provide strong evidence against a phonological account of poor letter-string processing in developmental dyslexia. Copyright © 2012 John Wiley & Sons, Ltd. KEY MESSAGES: Poor letter/digit-string processing in dyslexia can follow from either a phonological or a visual attention span disorder. The dissociation between letter/digit versus symbol-string processing was viewed as supporting the phonological account. Using three nameable stimuli types, Experiment 1 shows poor letter/digit-string processing but preserved colour-string processing in developmental dyslexia. Experiment 2 shows that the dyslexic's low performance in letter-string processing is not affected by a concurrent phonological task. These findings speak against a phonological interpretation of the disorder. The observed dissociation may well reflect a visual familiarity effect.